An Assessment of Rockbolting in Geogically Disturbed Mine Roadways - Reddish D. J; Whittaker B. N (The Australasian Institute of Mining and Metallurgy, 1992)
The rockbolting method of support is employed widely in several countries in different of mines. Hard rock mines use this method extensively. Soft rock mines, such as coal mines, have employed standing supports (steel sets) as the main method, although some countries such as the U.S.A. and Australia have preferred rockbolting. There is increasing interest in extending the rockbolting method in coal mines. The application of rockbolting techniques in an industry which traditionally has not applied such techniques, has required the development of a systematic design approach. This design approach uses extensive monitoring, to asses the viability of the support system in differing conditions. Currently at a number of new and existing mine developments in the U.K., rockbolting is being successfully applied. Although, inevitably some localised geotechnical problems have been encountered and have needed to be taken into account. The effect of faulting on roadway conditions is discussed in this paper and a design approach has been applied using a numerical analysis method, namely the Finite Element Method. The results presented in the paper serve as a useful guide to roadway support designers, and in particular the role played by different bolts in a range of conditions.